Electrochemical investigations on the capacity of flavonoids to protect DNA against damage caused by textile disperse dyes - Uliana, Carolina Venturini [UNESP]; Garbellini, Gustavo Stoppa [UNESP]; Yamanaka, Hideko [UNESP] (Elsevier B.V., 2014)
In previous work, the interaction of DNA with the textile dyes Disperse Orange 1 (DO1) and Disperse Red 1 (DR1), and their electrolysis products, resulted in significant changes in the characteristic oxidation peaks of the guanine and adenine moieties of immobilized dsDNA, measured using pencil graphite electrodes. In order to evaluate the protective capacity of flavonoids and teas against DNA damage caused by the dyes, studies of the interaction of DNA with DO1 and DR1 were conducted in the presence of the flavonoids myricetin and apigenin. The flavonoids were able to protect adenine and guanine from interaction with the dyes, as shown by smaller decreases in current intensity. Solutions of green tea and chamomile tea also showed protective capacities. Using interaction times of 180 s, the adenine moiety current intensity decreased by 60% of the initial value after interaction with 1.0 x 10(-5) mol L-1 DR1 alone, but by only 8% when the same DR1 concentration was employed in a mixture with 5.0 x 10(-7) mol L-1 myricetin, and by no more than 1% in a mixture with chamomile tea. The results indicated that damage to the DNA molecule could be reduced by the presence of flavonoids as well as green tea and chamomile tea, which are natural sources of the flavonoids myricetin and apigenin, respectively. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: DNA biosensor; Interaction; Flavonoids; DNA damage; Oxidation